Effectiveness Of Scientific Learning Module Through Project Based Learning Model On Materials Of Processing Organic And Ororganic Waste - Taula Sari, Rona; Angreni, Siska (Publisher Cv. Inara, 2023)
Science Lesson is a subject that demands a lot of conceptual understanding, because in science learning, many students are faced with abstract concepts. Teachers need to direct the students through meaningful learning process that they experience themselves so as to apply knowledge in everyday life. Thus the use of science-based learning-based learning module is expected to increase student activity and learning outcomes. The research development model is a 3-D development model (tree D). The purpose of research is to produce learning module science- based project based learning on the material of organic and inorganic waste is effective. Data collection using validation sheet, practical and module effectiveness. The technique of data analysis is descriptive data, that is by describing the practicality of using science-based learning process-based learning module. Based on the result of research, it can be concluded that the learning module of IPA on organic and inorganic waste processing materials oriented project based learning including effective category in terms of student activity, student motivation and student learning outcomes.